Новітня історія України в пострадянських білоруських підручниках та посібниках (за матеріалами наукового повідомлення на засіданні Президії НАН України 26 грудня 2024 р.) - Артимишин, П.І. (Вісник НАН України, 2025)
У доповіді комплексно проаналізовано збірні образи України та українців у контексті новітньої історії, характерні для пострадянських білоруських підручників та посібників. Простежено трансформацію підходів білоруських авторів упродовж 1991—2024 рр. щодо Першої світової війни, Української революції 1917—1921 рр., становлення та існування СРСР, відродження незалежності України в 1991 р. та її розвитку в пострадянських умовах. Зазначено, що на відміну від російських істориків, які відразу після початку російського повномасштабного вторгнення до України оперативно почали вносити зміни в гуманітарні навчальні видання, в білоруській дидактиці історії, за винятком тенденційного видання 2022 р., присвяченого історії Другої світової війни, ці трансформації поки що є значно інертнішими. The report comprehensively analyzes the collective images of Ukraine and Ukrainians in the context of modern history, characteristic of post-Soviet Belarusian textbooks and manuals. The transformation of the approaches of Belarusian authors during 1991—2024 regarding the First World War, the Ukrainian Revolution of 1917—1921, the formation and existence of the USSR, the revival of Ukraine’s independence in 1991 and its development in post-Soviet conditions, including against the background of relations with the Republic of Belarus, is traced. It is noted that unlike Russian historians, who immediately after the full-scale Russian invasion of Ukraine began to promptly make changes to humanities educational publications, in Belarusian history didactics, with the exception of the rather biased 2022 publication dedicated to the history of World War II, these transformations are still noticeably more inert in terms of assessments of modern processes, and reprints of past educational materials and the creation of new history textbooks and manuals have not occurred in large numbers since 2022.